Rolf Reichert, Atlas histórico regional do mundo árabe; mapas e resumo cronológico (A Historical and Regional Atlas of the Arabic World; Maps and Chronological Survey). Universidade Federal do Bahía; Centro de Estudios Afro-Orientais, Salvador, Rio de Janeiro, 1969. - Makki, Mahmud (Estudios de Asia y África, 2006)
-